A Mobile Life: John Urry, 1946–2016. (December 2016) - Adey, Peter
John Urry (1946–2016) was an extraordinary, generous and compelling force. As is evident in the hundreds of tributes and testimonials to his memory gathered already, his work influenced so many people through his talks at conferences, his published words in the pages of journals and his many books, and in conversations across viva examination tables, PhD juries and supervisory meetings. This essay remembers John's contribution to the study of mobility and spatial theory more generally.